Early association football in Ireland: Embryonic diffusion outside Ulster, 1877–1882. Issue 1 (2nd January 2022) - Moore, Martin
ABSTRACT: Recent scholarship has revised the traditional account of the origins of association football in Ireland, pointing to previously unacknowledged processes of diffusion independent of the developments in Ulster that were ultimately successful in establishing the code as a formally organised sport. This article completes this picture by presenting further evidence of early association football activity outside Ulster. It examines this activity in each of the provinces of Leinster, Munster and Connacht and analyses the types of teams that were involved. It concludes that the economic and social character of Ireland outside Ulster – in particular the lack of leisure time among the non-industrial working classes, combined with the earlier diffusion of rugby football to those classes who did enjoy leisure time, and the unwillingness of organisers to utilise Sundays – militated against the mass uptake of the code at this time.